2010
DOI: 10.1016/j.ejcts.2010.01.047
|View full text |Cite
|
Sign up to set email alerts
|

Total port-access robot-assisted pulmonary lobectomy without utility thoracotomy

Abstract: Robot-assisted lobectomy has been reported elsewhere as a feasible technique for lobectomy. We report a modification of the previously reported technique using a complete port-access approach without utility thoracotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 2 publications
0
61
0
1
Order By: Relevance
“…The other groups also reported a three-arm technique with one utility port. 9,[15][16][17] Cerfolio et al reported a four-arm technique without a utility incision, while Veronesi et al included the incision. 5,8) Carbon dioxide (CO 2 ) insufflation to achieve maximal surgical exposure while compressing the lung away from the operative area may provide the benefit for thoracoscopic surgery.…”
Section: Indicationsmentioning
confidence: 99%
“…The other groups also reported a three-arm technique with one utility port. 9,[15][16][17] Cerfolio et al reported a four-arm technique without a utility incision, while Veronesi et al included the incision. 5,8) Carbon dioxide (CO 2 ) insufflation to achieve maximal surgical exposure while compressing the lung away from the operative area may provide the benefit for thoracoscopic surgery.…”
Section: Indicationsmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45] Thus, the author reviewed reports from Western countries on robot-assisted lobectomy containing perioperative data after 2006 ( Table 3). Regarding the surgical procedure, three robot arms were mainly used, and only Veronesi, et al, 39) and Cerfolio, et al 44) used four arms.…”
Section: Robot-assisted Lobectomy For Primary Lung Cancermentioning
confidence: 99%
“…Ninan and Dylewski [13] described a robotic lobectomy with three arms: the robotic camera port is placed in the 5th or 6th intercostal space, directly over the mid-fissure area. The two other ports are placed in the same intercostal space anteriorly and posteriorly, in order to avoid multiple intercostal neurovascular bundles.…”
Section: Techniquesmentioning
confidence: 99%